Silicon germanium tin alloys formed by pulsed laser induced epitaxy - Stefanov, S.; Conde, J. C.; Benedetti, Alessandro; Serra, C.; Werner, J.; Oehme, Michael; Schulze, Jörg; Buca, Dan; Hollaender, B.; Mantl, Siegfried; Chiussi, Stefano (Applied Physics Letters, 2012)
Pulsed lased induced epitaxy is used to obtain heteroepitaxial Ge 1-xSn x and Si 1-x-yGe xSn y alloys with graded composition on Si(001) substrates. The transition from Ge 1-xSn x to Si 1-x-yGe xSn y was achieved by varying the number of laser pulses accordingly with the level of intermixing between Si, Ge, and Sn. Melt duration, predicted by numerical methods, is experimentally confirmed by "in-situ" reflectivity measurements and relates, like the end reflectivity value, to the level of intermixing. The possibility to adjust concentration profiles through laser processing of Sn films on virtual germanium buffer layers for lattice engineering of Ge 1-xSn x and Si 1-x-yGe xSn y alloys on silicon substrates is demonstrated. © 2012 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-29